Growth Bioregulators in the Reproduction of Banana Seedlings (Musa AAA) in Thermal Chamber, Ecuador - Nava Luzardo, Juan Carlos; Jaramillo Aguila, Edwin Edison (Rev. Téc. Fac. Ing. Univ. Zulia, 2022)
Ecuador is an important producer and exporter of bananas, for which it is required to obtain healthy harvests and increase production at any time of the year, under controlled and safe conditions. For this reason, the objective of this research was to evaluate the effect of growth bioregulators on asexual reproduction of banana seedlings in a thermal chamber. The experimental design was completely randomized with eight treatments and three repetitions: T1, Alga 600; T2, Miro; T3, Hormonagro Ana; T4, Hormone 1; T5, Basfoliar Kelp; T6, Cytokin; T7, Basfoliar Algae and T8, distilled water. The variable evaluated was the number of shoots per corm. There were significant differences (p<0.05) of T4, T5, and T6 with respect to the other treatments, presenting a greater number of shoots per corm. In this way, the bioregulators Hormonagro 1, Basfoliar Kelp and Cytoquin presented the best effect in the reproduction of banana seedlings in a thermal chamber, with the obtaining of healthy materials and with a greater number of shoots; being a viable alternative for an adequate production at any time of the year, under conditions that can be controlled in the banana sector.